Characterisation of mechanical-electrical properties of graphene nanoplatelets filled epoxy as conductive ink - Salim, Mohd Azli; Mokhlis, Maizura; Masripan, Nor Azmmi; Md. Saad, Adzni; Sudin, Mohd Nizam; Dai, Feng; Naroh, Azmi (Science and Technology Research Institute for Defence, 2021)
With the accelerating pace of development in printed electronics, the fabrication and application of conductive ink have been brought into sharp focus in recent years. The discovery of graphene also unfolded a vigorous campaign on its application. The purpose of this study was to determine the effect of graphene ink when the heat was applied to obtain the optimised formula and prepare graphene conductive ink with good conductivity. In this paper, graphene conductive ink was prepared using a simple method involving mixing, printing, and curing processes to produce conductive ink according to the formulation. Different compositions of a mixture that contained filler, binder, and hardener were put inside a vacuum to remove bubbles and the ink was cured at 150°C for 30 minutes. This research also studied the effect of the temperature on electrical and mechanical properties, and surface roughness of the hybrid conductive ink using a varying amount of filler for graphene nanoplatelets (GNP) inks. The electrical and mechanical properties were assessed using a four-point probe complying with the ASTMF390 and a Dynamic Ultra Microhardness complying with the ASTM E2546-15. The experimental results demonstrated an improvement in electrical conductivity. GNP showed resistivity around 0.0456 Mohm/sq. The correlation between the material hardness with different percentages of filler loading for GNP ink with and without thermal effect conditions was presented. Both of the two GNP ink conditions exhibited similar graph trends, where the hardness was found to increase as the filler loading in the ink was increased.